A Photonics-Based Coherent Dual-Band Radar for Super-Resolution Range Profile - Shaowen Peng; Shangyuan Li; Xiaoxiao Xue; Xuedi Xiao; Dexin Wu; Xiaoping Zheng (IEEE Photonics Journal, 2019)
We propose and demonstrate a photonics-based coherent dual-band radar for super-resolution range profile in this paper. This radar cannot only generate coherent dual-band linear frequency modulated signals with large bandwidths, but also realize a paralleled coherent de-chirping processing to the dual-band echoes simultaneously based on a single compact photonics-assisted transceiver. The sharing of a single transceiver for signals with different bands ensures perfect stability and coherence among the waveforms, which makes it possible to realize a super-resolution range profile by fusion of dual-band signals without heavy computation on phase compensation. In the experiment, the radar operates in S-band with a bandwidth of 1.5 GHz and X-band with a bandwidth of 3 GHz, and results show its range resolution is up to 1.6 cm by coherent fusion processing, which is nearly corresponding to the resolution gotten by a linear frequency modulated wave with a bandwidth of 9.5 GHz ranging from 2 GHz to 11.5 GHz, much higher than the scenario when the radar is operated in the single-band mode. This technology would improve the accuracy of classification and recognition of the targets.